Prospectiva Estratégica Territorial en el Gad Parroquial Rural de Lican - María Soledad, Huilca Álvarez (2022)
AbstracIn this research, the development challenges of the parish of Lican and the problems that should be prioritized to achieve economic, social and sustainable development are shown. This was achieved through a descriptive type of research and based on the collection of information through surveys, interviews, and workshops with representatives of the GAD of Lican. It should be noted that the GAD of Lican played a very important role in carrying out this research. Hence, five key variables were established: Strengthen budgetary and financial resources and public services, guarantee food security for all inhabitants, prevent natural disasters in Lican, consolidate productivity, labor stability and income, and develop technological infrastructure. Based on the stakeholder analysis, two hypotheses were finally defined: to strengthen budgetary, financial, and public service resources and to develop technological infrastructure. From these two hypotheses, 4 different scenarios were proposed, where the scene with the highest probability of occurrence was the first one, in which both hypotheses are fulfilled. Therefore, the document ends with a proposal of three strategic objectives along with their respective actions and challenges to be faced to achieve the optimal scenario by 2030 and concludes that the territorial foresight in Lican was carried out adequately and allowed having a clear picture of what is necessary to achieve economic, social and sustainable development.